2015
DOI: 10.1007/s12011-015-0490-5
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Metabolites and Methylation Capacity Among Individuals Living in a Rural Area with Endemic Arseniasis in Inner Mongolia, China

Abstract: More than 0.3 million individuals are subject to chronic exposure to arsenic via their drinking water in Inner Mongolia, China. To determine arsenic methylation capacity profiles for such individuals, concentrations of urinary arsenic metabolites were measured for 548 subjects using high-performance liquid chromatography and a hydride generator combined with inductively coupled plasma-mass spectrometry. Mean urinary concentrations of dimethylarsonic acid (DMA), monomethylarsonic acid (MMA), inorganic arsenic (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…There is wide evidence demonstrating that some individuals are more susceptible to As [ 102 , 103 ], and genetic factors can also play a role in susceptibility [ 104 , 105 ]. The factors we found to be associated with the urinary profile of As are supported by the scientific literature: consumption of seafood [ 48 , 79 , 83 , 90 , 91 , 94 , 96 , 98 , 99 ], consumption of contaminated tap water [ 30 , 94 , 97 ], occupational exposure [ 87 , 96 ], and some polymorphisms [ 97 , 100 , 101 ]. We also identified some other factors, such as wine, grains, meat, and milk consumption, which make for interesting further investigations.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…There is wide evidence demonstrating that some individuals are more susceptible to As [ 102 , 103 ], and genetic factors can also play a role in susceptibility [ 104 , 105 ]. The factors we found to be associated with the urinary profile of As are supported by the scientific literature: consumption of seafood [ 48 , 79 , 83 , 90 , 91 , 94 , 96 , 98 , 99 ], consumption of contaminated tap water [ 30 , 94 , 97 ], occupational exposure [ 87 , 96 ], and some polymorphisms [ 97 , 100 , 101 ]. We also identified some other factors, such as wine, grains, meat, and milk consumption, which make for interesting further investigations.…”
Section: Discussionsupporting
confidence: 76%
“…In Inner Mongolia, in an endemic area for As poisoning where the groundwater typically contains high As concentrations of up to 1354 μg/L, with a mean value of 173 µg/L, the mean u(iAs+MMA+DMA) concentration was 300.17 µg/L [ 30 ]. In the same area, another study found mean u(iAs+MMA+DMA) concentrations of 252.84 µg/L [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Arsenic enters an organism via the respiratory tract, alimentary canal, and skin, and it is primarily metabolized in the liver [ 3 ]. The metabolic pattern has primarily been regarded as occurring through oxidative methylation [ 4 ], which was formerly considered a detoxification pattern [ 5 ]. However, monomethylarsonous acid (MMA III ) and dimethylarsonous acid (DMA III ) have recently been shown to be more poisonous than inorganic arsenic (iAs) [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%